A prospective assessment of adequacy of orthopaedic emergency medicine consultations: The experience at an academic level I trauma center. Issue 2 (March 2020) - Kusnezov, Nicholas; VanTienderen, Richard J.; Prabhakar, Gautham; Dunn, John C.; Rensing, Nicholas; Eisenstein, Emmanuel D.; Abdelgawad, Amr A.
Abstract : Background: This study sought to determine the diagnostic accuracy, consultation appropriateness, and effectiveness of management of orthopaedic conditions in an emergency setting. Methods: A prospective, blinded analysis of all orthopaedic consults by emergency medicine providers at our institutional level I trauma center was conducted between May 1, 2016 and Jun 30, 2016. Providers were blinded to eliminate Hawthorne effect bias. Direct orthopaedic transfers and general surgery trauma consults were excluded. The accuracy of the initial diagnosis, effectiveness of management by the emergency medicine physician, and ultimately, consult appropriateness were evaluated. Results: The emergency department received 239 consecutive consults over the 2-month period. Of these 38.5% (92/239) were inaccurate due to nonspecific consults (14.6%; 35/239), incomplete information with missed injuries (12.6%; 30/239), grossly incorrect diagnosis (11.3%; 27/239), or use of incorrect terminology (5.9%; 14/239). Inaccurate diagnoses led to a significant change in orthopaedic management in 73.9% (68/239) of patients. Of the open injuries, 30.8% (4/13) were incorrectly called "closed." Antibiotics were not initiated prior to orthopaedic consultation for open fractures in 61.5% (8/13) of patients. Initial work-up was incomplete in 25.5% (61/239), affecting management in 44.3% (27/61) of cases; 56.9% (136/239) of consults required acute orthopaedic intervention in the emergency department setting. Conclusions: In this study a significant number of patients presenting to a level one trauma center referred for orthopaedic consultation by emergency medicine providers were initially misdiagnosed and suboptimally managed. This may have a significant impact on patient morbidity and mortality. Orthopaedic consultants must be vigilant and apply due diligence to ensure that emergency patients receive proper and thorough evaluation and treatment. Level of Evidence: Level IV.